1993
DOI: 10.1016/0550-3213(93)90131-8
|View full text |Cite
|
Sign up to set email alerts
|

On the spectrum and scattering of W3 strings

Abstract: We present a detailed investigation of scattering processes in W 3 string theory. We discover further physical states with continuous momentum, which involve excitations of the ghosts as well as the matter, and use them to gain a better understanding of the interacting theory. The scattering amplitudes display factorisation properties, with states from the different sectors of the theory being exchanged in the various intermediate channels. We find strong evidence for the unitarity of the theory, despite the u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
97
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(104 citation statements)
references
References 23 publications
(181 reference statements)
7
97
0
Order By: Relevance
“…The BRST charge for W 3 string was first constructed in [6], and the detailed studies of it can be found in [6][7][8][9][10][11][12]. A natural generalization of the W 3 string, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The BRST charge for W 3 string was first constructed in [6], and the detailed studies of it can be found in [6][7][8][9][10][11][12]. A natural generalization of the W 3 string, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Note that Q V ir is just the usual Virasoro BRST operator for the matter plus spin-(3,4) ghost systems. The BRST operator in this special basis is the generalisation to W 4 of the W 3 BRST operator of [10], which was obtained from the original one [18] by a canonical redefinition of the fields. The spin-four part Q 2 was in fact already given in [13].…”
Section: The W 4 Stringmentioning
confidence: 99%
“…This relation is clarified by going to a new basis of fields introduced in [10]. In this new basis, a special subsector of the W 3 model was seen to correspond to the Ising model [11], see also [12,10,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above numerology, it was suggested in [4] that the above noncritical W 3 -string should in some sense contain a critical Virasoro string with 26 free scalars. After the work of [4] it was shown [6] that, by going to a new basis in the Hilbert space, the BRST operator of the W 3 -algebra can be written as the sum of two, mutually anticommuting, nilpotent BRST operators…”
Section: Introductionmentioning
confidence: 99%